A review of contract farming and factors that impinge youths acceptance to contract farming - Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Uli, Jegak; Abu Samah, Bahaman (Eurojournals, 2009)
The growing body of literature associated with contract farming had examined its relevance and relationships between a number of variables in order to gain a better understanding on being involved in contract farming and agriculture in general. Youths acceptance of contact farming is an important element to the successful implementation of this farming method in agriculture. Thus, it is significant to draw to attention to the factors that affect youths participation in contract farming and its implications to policy development strategies. This article would be useful for future researchers who are seeking directions to further examine the determinants of youths acceptance of contract farming.